Arquitetura de serviços integrada para promover a economia circular na agricultura 4.0 - Varella, Walter Augusto (2022)
The increase in world population in recent years, with expectation to reach 9 billion in 2050, has impacted the Agriculture by requiring to increase productivity in the same agricultural areas. The challenges as more demanding consumers, population concentrated in urban regions, reduction of inputs such as water and energy, soil nutrient conditions and climatic factors not always favorable. In this context, the digital revolution in agriculture using Industry 4.0 technologies enables the development of agricultural scenarios, with sensors collecting data about environmental characteristics, soil, water quantity, plantation, and with these data stored on cloud servers. These data are analyzed by using tools from the Big Data ecosystem, Artificial Intelligence algorithms and machine learning, transforming data into information that allows farmers to make operational and strategic management decisions more assertively. Thus, Agriculture 4.0, using Industry 4.0 technologies, takes digitization to farms that become more intelligent, by using management systems accessible through the Web, autonomous irrigation and fertilization controls, planting and harvesting made with agricultural machinery, robotic systems and embedded intelligence, with increased productivity and quality, and with it economic, environmental and social benefits. This research sought to identify which Industry 4.0 technologies are being adopted in Agriculture, and after a Systematic Literature Review a Services Architecture was proposed to promote Circular Economy in Agriculture 4.0 and strategic actions with the ReSOLVE framework. This work contributes to the theory with systematized knowledge about technologies applied in Agriculture 4.0, providing new possibilities for research. The contribution to practice is the conceptual proposal of the Service Architecture that which provides for third-party opportunity to develop hardware and software, and as a contribution to society is the promotion of the Circular Economy in Agriculture, with environmental and economic benefits, reducing waste of food, food insecurity and social gains.